"The Care of the Self” Practice in a Contemporary Culture - Petrova G. I. Galina Ivanovna; Gural A. K. Anton; Brylina I. V. Irina Vladimirovna; Kornienko A. A. Alla Alexandrovna; Stupnikova O. B. Olga Borisovna (2017, 2017)
Title screen